Efficacy of "mucoregulatory" agents in Young's syndrome. Issue 6 (June 1988) - Currie, D C; Greenstone, M; Pavia, D; Agnew, J E; Pellow, P; Clarke, S W; Hendry, W F; Cole, P J
Abstract : Eight patients with Young's syndrome were treated with four "mucoregulatory" agents for eight weeks in a randomised, open crossover study. There was no improvement in tracheobronchial clearance, pulmonary function, or sperm count.